(3GdCaYGd hJUGQjagGs - (3Ydj Hf LYaQ Hf Ydj GdSYOj, CHh GdbGSe, GdSYOj GdUbdj GdeUQj, GdeYQha H GHf GdbWGY,J (B515 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdYRI hGdSdWGf SCdJfi CQGc Gddg GdShd hHdZc GdeCehd Cf CdNU dc eG EfZdb hHYO hCNdU dc eG YSQhG hGfYbO ef cJGH CHfjI GdCaYGd dCHi HcQ eMeO Hf YeQ Hf YHO GdYRjR s
(3BNQgG (B:s
(3HGH GdKfGA ai GdecQQ ced GdcJGH HMhd Gddg hbhJg hGdMeO ddg Ydi JJeJg hGdUdGI GdeHGQcI Ydi fHjfG eMeO BNQ GdeQSdjf hYdi Bdg hCUMGHg GdWjHjf GdWGgQjf hSde JSdjekG s
(3GdfSNI HgG MhGTs
(3fSNI fajSIs
(3HgGeTgG JbjjOGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas